Analysis of the role of price in the influence of e-ticketing and e-service quality on visitor satisfaction at Sam Poo Kong, Semarang City - Aswan, Mukhamad Kholil (Trigin Publisher, 2025)
This study focuses on the influence of E-ticketing and E-service quality on visitor satisfaction mediated by price at Sam Poo Kong, Semarang City. The purpose of this study is to see the influence of E-ticketing on price, the influence of e-ticketing on visitor satisfaction, the influence of E-service quality on price, the influence of E-service quality on visitor satisfaction and the influence of price on visitor satisfaction. This study uses a quantitative method with the research population being all visitors to Sam Poo Kong and using 250 samples spread across various places and who have visited Sam Poo Kong Semarang. This study uses an analysis technique with Structural Equation Modeling (SEM) Amos. The results show that e-service quality (p <0.001) and price (p <0.001) have a significant effect on visitor satisfaction and e-ticketing has no effect (p>0.05). The model shows a good fit (RMSEA = 0.09; CFI = 0.972). This study is the first to examine the role of price mediation variables in the context of cultural tourism in Indonesia and provides practical insights for managers to improve the quality of digital services and communication strategies in e-ticketing.